Prostate-specific Antigen at 3 Months as a Predictor of Radiologic Progression-free Survival in Metastatic Hormone-sensitive Prostate Cancer Treated with Apalutamide: Analysis of 633 Patients in a Real-world Database - Mario Hassi Roman; Kinga Mate; Pedro De Pablos-Rodriguez; Álvaro Zamora Horcajada; Ana Guijarro Cascales; Ángeles Sanchís Bonet; Antoni Vilaseca; Darío Vázquez-Martul Pazos; Estefanía Linares Espinós; Jesús Muñoz Rodríguez; José Manuel de la Morena Gallego; José Ramón Alemán; et al. (European Urology Open Science)
Background and objective: The depth of the prostate-specific antigen (PSA) decline after androgen receptor pathway inhibitor (ARPI) treatment combined with androgen deprivation therapy for patients with metastatic hormone-sensitive prostate cancer (mHSPC) may affect prognosis. The primary objective in our study was the correlation between the PSA response at 3 mo and radiologic progression-free survival (rPFS) at 24 mo. Three groups were defined according to the PSA decline: complete response (PSA ≤0.02 ng/ml), partial response (PSA >0.02 and ≤0.2 ng/ml), and incomplete response (PSA >0.2 ng/ml). Secondary objectives were correlation between the PSA response at 3 mo and overall survival, and the development of a model predicting complete PSA response. Methods: We conducted a retrospective multicenter study of patients with mHSPC treated with apalutamide from May 2018 to September 2023 registered in the Real-World Evidence APA registry across 20 centers. Key findings and limitations: We included 633 patients with mHSPC. The median age at diagnosis was 68 yr (interquartile range [IQR] 63–75) and median PSA was 16 ng/ml (IQR 7.5–64). Some 63% of the short had low-volume disease, 51% had de novo disease, 48% had recurrent disease. At 3 mo, 27% had a complete response, 42% a partial response, and 31% an incomplete response, with corresponding rRFS rates at 24 mo of 92%, 86%, and 63%. According to the predictive model, a complete PSA response at 3 mo was associated with the use of next-generation imaging and PSA <50 ng/ml at diagnosis. Study limitations include heterogeneity among the groups and variations in data quality and assessment methods. Conclusions and clinical implications: Patients with a complete PSA response after 3 mo of apalutamide treatment face a very low risk of progression within 2 yr. Conversely, nearly 50% of patients with an incomplete PSA response will experience disease progression. Patient summary: For patients with metastatic prostate cancer that is still responsive to hormone therapy, a complete response after treatment with a drug called apalutamide is associated with a very low risk of progression within 2 years. However, nearly half of patients with an incomplete response to apalutamide will experience progression of their cancer.